Analisis Faktor Determinan Kinerja BPRS di Indonesia Periode 2011-2019 - Sunu Prasetya Adi; Muhammad Ghafur Wibowo (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The main objective that BPRS have is to maximize their performance. Several problems that can disrupt the performance of BPRS are the characteristics of BPRS which not providing payment traffic services, and total assets, total financing and Third Party Funds (DPK) that BPRS have are lower than other types of Islamic banking. This study aims to analyze the factors that can affect the performance of the BPRS. This study uses 31 BPRS in Indonesia, where all data is obtained from the December quarterly reports of each BPRS on the website of the Financial Services Authority (OJK) with the period 2011 to 2019. The data analysis technique used in this study is panel data regression analysis. The results of the study found that the variables that had a significant influence on the performance of the BPRS were total assets, NPF and CAR.